Case histories of organizational efforts of small-scale fishermen in Butuan Bay. - Martinez, Mark B.
The case histories of two fishing villages and the associations therein presents the fishers as part of the fisheries sub-sector called small scale. This study recognized the need to raise the standard of living in the impoverished small-scale fishing communities in the country. Aside from this, small-scale fishers also face the threat of the destruction and degradation of their resource- the sea., In the past few decades, organizations among fishers have begun to arise in the country in order to confront related issues. These fisherfolk organizations can be evaluated in relation to their being examples of community organization, rural organization, and people's organization. The organizational processes that took place in the selected fishing villages are similar. The basic steps used in the organizing the fishers are entry into the community by the organizer, contact building and core group formation, formation of the organization, problem and resource identification, and the taking of actions regarding the identified problems. Important features of a rural organization were used as important determinants of the fisher organizations' performance. Being organized by a single agent, the two associations did not differ in their origin and history; principles; leadership; membership qualifications, obligations, and rights; and, benefits and privileges. The notable difference between the two fisher association is in their objectives. The first association has a more simple and specific objective from which they based all their subsequent programs while the other one has a very broad objective. Problems of the first association include perceived failure of their project, inadequate monitoring and maintenance of their project, and a flawed leadership. At present, there are only fifteen (15) members remaining in the association. Regarding their prospects, the association can still become or join a people's organization because it passed in almost all of their criteria identified in evaluating PO's, although it could not be said that the association did improve the lives of the fishers. On the other hand, the second association's problem include lack of fund and support for their fishery law enforcement functions and failure to achieve their goal of availing loan for them to upgrade their vessels and gears. At present, it is no longer active. Also, the association failed in almost all of their criteria identified making the association far from becoming a people's organization.